The Effect of Ease of Access, Promotion, And Brand Ambassador On Buying Interest In E-Commerce Lazada - Sofi Salsabila; Moh. Muklis Sulaeman; Diah Ayu Novitasari; Moh. Heru Budi Santoso (RTTM, 2024)
The facilities and ease of access offered by e-commerce are important factors in shaping consumer buying interest in e-commerce transactions. E-commerce also uses social media and brand ambassador to carry out promotions aimed at helping consumers become interested in buying these products. This research aims to determine the influence of ease of access, promotions and brand ambassadors on purchasing interest in Lazada E-commerce. The population in this study is male and female consumers aged 18-45 years, have the Lazada application and have shopped on the Lazada application at least once. Meanwhile, the sample consisted of 100 respondents from the people of Lamongan City, with the technique used being non-probability sampling and also the purposive sampling method. The results of this research using the t test show that ease of access has a significant effect on purchase interest, promotion has a significant effect on purchase interest, and brand ambassador have no effect on purchase interest. The results of the research using the f test show that ease of access, promotion and brand ambassadorship have a significant effect on purchasing interest in Lazada e-commerce.